PENDIDIKAN DALAM ALQURAN (KAJIAN PERAN FAKTOR AJAR) - Hasibuan, MUslim (FORUM PAEDAGOGIK, 2014)
ABSTRAKAl-Quran and Hadith have laid the foundations of the affairs of the world and the hereafter, and they have no exception educational affairs. If the Koran is believed to be the handle and instructions, in which there is certainly teachings or instructions to educate children, and instructions referred to illustrate the strong involvement and teaching basic factor in the process of education and other forces that are called by a factor of guidance from Allah. Basic factors referred to in this paper are innate factors or transcription factors; and other terms also called immortal factor, talent, and potential, and religious terms called fithrah factor. While teaching in question is a factor influencing factors originating from outside of the human in the household, in the community, in schools and in other places. When viewed in terms of education, environmental factors (teaching), we can determine one's personal formation. One example of the inability of humans to develop the ability of the environment is essentially no role Cain, he was desperate after killing his brother Abel; Cain did not know how to treat his brother's corpse. But after he saw crows picking at his plant soil that kills, Cain immediately was able to solve his problems, which he was able to grow his brother's body. There was an educational process that is stimulated by factors of teaching (crows picking at the ground or sand). Some verses and the explanation can be found that no matter how strong the influence of evil from the outside (event Masithah with Pharaoh) is helpless if we receive guidance from Allah. And on the contrary, however, the influence of good thing that comes from the outside (the event with her son Noah) has no effect if God did not give him guidance. So there are three main factors that affect the education of children, which is the basic factor, teaching, and guidance from Allah.Keywords: Basic and Festive factors and Hidayah